2009
DOI: 10.1097/mpg.0b013e31819a4e1a
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices and Associated Factors Through the First 9 Months of Life in Bavaria, Germany

Abstract: Further improvements in nutrition of infants may be achieved in 2 ways: promotion of breast-feeding according to current recommendations and better counselling on the correct timing of introduction of semisolid food-especially for parents of not- or short-time breast-fed babies and focused on young mothers with low levels of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
58
3
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 28 publications
18
58
3
13
Order By: Relevance
“…The Dutch health care system recommends introducing complementary food between the ages of 4 and 6 months. The present results, and those from other studies (22,37,43) , show that mothers from African descent are less likely to follow these guidelines and introduce complementary food earlier. This infant feeding pattern, e.g.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The Dutch health care system recommends introducing complementary food between the ages of 4 and 6 months. The present results, and those from other studies (22,37,43) , show that mothers from African descent are less likely to follow these guidelines and introduce complementary food earlier. This infant feeding pattern, e.g.…”
Section: Discussionsupporting
confidence: 74%
“…We selected healthy infants with a normal and appropriate pregnancy outcome to comprise a healthy study population, due to exclusion of pre-term born and small-for-gestational age children. Furthermore, we analysed growth in weight, length and weight-for-length and were able to include many known risk factors for early growth (37) . The present study is one of the first to investigate ethnic differences in growth in weight and length in infancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of interest that the association between breast-feeding and the healthy, meat and vegetable pattern was independent of education, which was associated with this pattern as well. Other studies have reported positive associations between breast-feeding and education (49,50) , and women who breast-fed for .16 weeks were more often highly educated (51) . In the latter study, breast-fed children were less likely to have a low consumption of fruit and vegetables and a high consumption of snacks or an unhealthy diet, independent of maternal education (51) .…”
Section: Discussionmentioning
confidence: 99%
“…Less than one-third of [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] months old children met the minimum criteria for dietary diversity [8,9], and only 50% received the minimum number of meals and only 21% of children aged 6-23 months met the minimum criteria [9]. Infant formula supplementation at any age is uncommon in Ethiopia [10].…”
Section: Introductionmentioning
confidence: 99%